RESISTENSI PETANI TERHADAP INOVASI BUDIDAYA BAWANG MERAH DI LERENG GUNUNG SUMBING TEMANGGUNG - Iin Setyowati; Roso Witjaksono; Rahima Kaliky (University of Jember, 2020)
Shallots are a potential commodity in mountainside of Sumbing in Temanggung Regency, but the average productivity of local farmers' always lower than yield potential of shallots Newly Pre-eminent Verieties planted. The low productivity due to the local farmers are not implementing innovation on shallot cultivation and they have been identified as resistant behavior. The study aimed to identify the level of resistance of farmer to innovation technology of shallot cultivation and to find out the factors that affect resistance. The study used Mixed Method approach by promoting quantitative approach as its survey method. The study conducted in Legoksari, Pagersari and Losari Villages of Tlogomulyo District and in Tanggulangin, Jetis and Ngaditirto Villages in the Selompampang District. The research samples were 105 respondents, they were selected by simple random sampling chosen deliberately. Data were analyzed by multiple linear regression tests. Research results showed: (1) the number of farmers who have high resistance to innovation technology of shallot cultivation s less than 50%, and (2) farmers' resistance influenced by knowledge, subjective norms, and attitudes. Another factor that causes resistance is that shallots are not the main commodity cultivated by the farmers. The policy that can be implied from this study is the increasing role of adopter farmers'in improving knowledge, subjective norms and farmers' attitudes towards shallot cultivation. Keywords: shallot, innovation, farmers